Factors That Influence Millennials' Interest In Saving In Shariah Banks - Jairin, Jairin (Fusshilat : Jurnal Studi Pendidikan dan Keislaman, 2024)
This study aims to analyze the factors that affect students' interest in saving at Islamic banks in Bima. These factors are religiosity, sharia economic knowledge, digital promotion and services. This study uses primary data by providing a questionnaire to 100 students in Bima. Using subjects on 3 campuses in Bima, namely Umbo, Nggusu Waru Bima University, Muhammadiyah Bima University, to find out the interest in saving using Islamic banks. The method used is Multiple Linear Regression with IBM SPSS 26 as the data processing tool. Based on the analysis and testing that has been carried out, results are obtained that show that the variables of sharia economic knowledge and promotion have a significant positive effect on students' interest in saving. However, the variables of religiosity and digital services did not have a significant and positive effect on students' interest in saving at Islamic banks in Bima.